Sportmen’s experiences at a somatology clinic receiving a sport message - Karien Jooste; Valencia Khumalo; Jeanette Maritz (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2013)
Sportsmen are increasingly visiting somatology clinics for massages prior to an aerobic sports event. Massage is frequently utilised prior to an athletic activity, as a means of enhancing performance. Massage is known to have both calming and stimulating properties, thereby possessing the potential to benefit performance in numerous different circumstances. In the context of sportsmen visiting somatology clinics, it is unclear how men experienced the benefits of a massage by a therapist in the somatology environment, prior to participating in an aerobic sports event. The purpose of this qualitative, exploratory, descriptive and contextual study was to explore and describe the experiences of men regarding sports massage in a somatology clinic prior to an aerobic sports event. Purposive sampling was used to select eight (8) men, aged between 25 and 50 years, who received two massages within two weeks prior to participating in an aerobic sports event. The data were collected through in-depth, unstructured, individual interviews and field notes until saturation of data was achieved. Trustworthiness was ensured by utilising the principles of Lincoln and Guba’s model. The men experienced the sports massage as relaxing and giving perceived holistic beneficial effects. They described their experience during the massage and during and after participation in an aerobic sports event. A sports massage brings about psychological, physical, and spiritual effects during and after participation in an aerobic sports event.